Mechanical Characteristics of Polylactic Acid Nanosheet Prepared by Gravure Printing Method - Shunsuke, Nakano; Makio, Tamada; Mohd Danial, Ibrahim; Masayuki, Ochiai; Satoru, Iwamori (The Materials Science Society of Japan, 2025)
The objective of this study is to investigate the physical properties of polylactic acid (PLA) nanosheets. Due to their extremely large surface area relative to thickness, nanosheets can conform to complex, uneven surfaces without the need for adhesives. Consequently, PLA nanosheets have been proposed as potential substrates for wearable devices and as alternatives to sutures in surgical applications. To support such applications, it is essential to understand the frictional behavior between nanosheets and human skin. In this study, poly-L-lactic acid (PLLA) and poly-DL-lactic acid (PDLLA) nanosheets with thicknesses ranging from 25 to 200 nm were fabricated using a roll-to-roll production process incorporating gravure printing. The fundamental properties of the resulting thin films, including crystallinity, elastic modulus were systematically characterized. Furthermore, the coefficient of friction between these PLA nanosheets and human skin was evaluated using a force transducer, to elucidate the underlying contact mechanics.